Evaluating The Perceived Effects Of Total Quality Management (Tqm) Training Program In Tenaga Nasional - Haron, Khalidah (1995)
Tenaga Nasional Berhad (TNB) was corporatized on the 1st. of September 1990. To help achieved its new corporate mission, total quality culture now forms a major aspect of TN B's strategic initiative. Management has turned to the training and development specialist to improve the organization's capabilities through TQM training program. Before TNB was corporatized , training and development can be viewed traditionally as a discretionary expenditure. Now that it is a corporate body, for TNB to stay in business, they need to start rapid savings by reducing spending not directly related to improving their profit margin. If training can not show positive, unambiguous results, organization will